EXPERIMENTAL EVALUATION OF ANTIDEPRESSANT ACTIVITY OF AQUEOUS AND CHLOROFORM LEAF AND SHOOT EXTRACTS OF EICCHORNIA CRASSIPES LINN IN MICE - Uppala, Praveen Kumar; K, Atchuta Kumar; Patro, Sujit Kumar; B, Murali Krishna (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To investigate antidepressant activity of aqueous and chloroform extract of Eicchornia crassipes plant leaves and shoots in mice. Methods: The antidepressant activity of aqueous and chloroform extract of Eicchornia crassipes plant leaves and shoots were tested by forced swim test (FST) and tail suspension test (TST) in albino mice and the results were compared for the both extracts. Imipramine was used as the standardrug for comparison. Results: Phytochemical screening showed presence of carbohydrates, alkaloids, flavanoids, steroids, saponins, amino acids, gums and mucilage. aqueous extract of Eicchornea crassipes (AEEC) and chloroform extract of E. crassipes (CEEC) did not produce any lethal effect even upto 2000 mg/kp.o during acute oral toxicity study. In FST and TST, CEEC showed diminution of duration of immobility time in 200 mg/kg but not in 100 mg/kg. Conclusion: From the above finding concluding that, shortening of immobility time in the FST and TST indicating, CEEC showed more antidepressant activity acting either by the enhancement of central 5-HT or catecholamine neurotransmission compared to AEEC in mice. Keywords: Eicchornia crassipes, Aqueous extract of Eicchornia crassipes, Chloroform extract of Eicchornia crassipes, Forced swim test, Tail suspension test.